THE INFLUENCE OF MARITAL PROPERTY AND LIFE-ADJUSTMENT TO THE QUALITY OF LIFE OF SINGLE FAMILY DURING THE COVID-19 PANDEMIC - Mira Fauziyya Fatihanna; Herien Puspitawati (Journal of Child, Family, and Consumer Studies, 2023)
The divorce rate in Indonesia is increasing along with the Covid-19 pandemic that is sweeping the entire world. West Java has the worst divorce rate in Indonesia, with 102,151 divorce cases. Implementing social distancing and workers from home (WFH) set by the government makes the burden borne by single mothers heavier. This study aims to analyze the influence of Marital Property and life adjustment on the quality of life of a single-family during the Covid-19 pandemic. A functional, structural approach and social conflict theory were used in this study. This research design is a cross-sectional study with online questionnaire tools. The research sample of 65 people was selected by voluntary sampling in West Java. This study found a correlation and effect between marital property and life adjustment on quality of life. The results of the typology analysis of each variable are in a low category.